Strategies for Improving Education Quality Management Towards World-Class Education - Ade Sofa; Kasful Anwar Us; Fridiyanto , Fridiyanto (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This study explores the strategies implemented by Universitas Islam Indonesia (UII) in enhancing educational quality management as part of its pursuit toward becoming a World Class Education (WCE) institution. Using a qualitative descriptive method, the research focused on the Faculty of Islamic Studies (FIAI), including academic programs and supporting units engaged in quality initiatives. Data were gathered through interviews, document analysis, and observation of quality assurance practices. The findings reveal that UII has established a robust Quality Management System (QMS) grounded in continuous improvement, stakeholder involvement, and digital integration. Leadership at multiple institutional levels plays a transformative role in aligning vision and operational goals. Furthermore, collaboration with international partners and participation in accreditation processes have elevated institutional performance and visibility. Despite existing challenges, UII's strategies in quality assurance—rooted in both Islamic values and global best practices—represent a strong foundation for sustainable academic excellence in the international arena.